Contribution of fine particulate matter to present and future premature mortality over Europe: A non-linear response. (August 2021) - Tarín-Carrasco, Patricia; Im, Ulas; Geels, Camilla; Palacios-Peña, Laura; Jiménez-Guerrero, Pedro
Highlights: Premature mortality associated to fine particles (PM2.5 ) over Europe is estimated. Excess mortality rate from PM2.5 in Europe is 904, 000 premature deaths/year. This mortality rate will increase by 73% in the year 2050 under RCP8.5 scenario. Increase in premature mortality is associated fundamentally to the aging of population. Abstract: The World Health Organization estimates that around 7 million people die every year from exposure to fine particles (PM2.5 ) in polluted air. Here, the number of premature deaths in Europe from different diseases associated to the ambient exposure to PM2.5 have here been studied both for present (1991–2010) and future periods (2031–2050, RCP8.5 scenario). This contribution combines different state-of-the-art approaches (use of high-resolution climate/chemistry simulations over Europe for providing air quality data; use of different baseline mortality data for specific European regions; inclusion of future population projections and dynamical changes for 2050 obtained from the United Nations (UN) Population Projections or use of non-linear exposure–response functions) to estimate the premature mortality due to PM2.5 . The mortality endpoints included in this study are Lung Cancer (LC), Chronic Obstructive Pulmonary Disease (COPD), Cerebrovascular Disease (CEV), Ischemic Heart Disease (IHD), Lower Respiratory Infection (LRI) and other Non-Communicable Diseases (other NCDs). Different risk ratio and baseline mortalities for each disease end each age range have been estimated individually. The results indicate that the annual excess mortality rate from fine particulate matter in Europe is 904, 000 [95% confidence interval (95% CI) 733, 100–1, 067, 800], increasing by 73% in 2050s (1, 560, 000; 95% CI 1, 260, 000–1, 840, 000); meanwhile population decreases from 808 to 806 million according to the UN estimations. The results show that IHD is the main cause of premature mortality in Europe associated to PM2.5 (around 48%) both for the present and future periods. Despite several marked regional differences, premature deaths associated to all the endpoints included in this study will increase in the future period due to the climate penalty but especially because of changes in the population projected and its aging.